مقدار عوض الخلع في رأي القاضي محمد الخضري الأشنوي(ت: 1997م) (دراسة تحليلية) - محمد, ‌ أ.م. د. شەماڵ عبدول; محمد, م. كامران جمال (Sulaimani Journal for Humanities, 2023)
My study is entitled: (The amount of compensation obtained by a husband for khul from Judge Muhammad Khudhri Shnoyi’s perspective). It discusses the meaning and purpose of ‘khul’ (breaking the marriage relationship with the wife's willingness to pay compensation to her husband or by returning the dower (mahr) to him), and the evidence for the legitimacy of khul from the Sharia law. Then it considers the Islamic scholars’ opinions on whether it is permissible for a husband to receive this compensation or dower from his wife in exchange for divorcing her, or whether it is impermissible. If the answer to the former is yes, is it necessary for compensation to be the same amount as the dower or is it permissible to be more or less than that according to the Sharia law? Regarding each one of these points, I have referred to the Islamic scholars’ opinions, and then I have discussed whether khula is permissible only in exchange for a material gain or whether it can be done without any material gain. Finally, I concluded my study with Judge Mohammad Khudhri’s opinion and mentioned some other strong opinions on this issue. In addition, both methods of identification and analytical analysis are used in the study. The main purpose of this study is to answer the above questions. The most important conclusions are that most Islamic jurists agree that it is permissible to have a material gain in a divorce i.e. khul is valid according to the majority of scholars, but there is a difference in the amount of the gain, and whether it is permissible to differ in the amount of dowry. However, what Judge Mohammad Khudhri supports is that the husband must receive these benefits and compensation with the consent of his wife, but if his wife does not agree, it is not permissible to receive them. Even after her consent, it must not be more than her dower; and I have also chosen and supported this opinion due to the strength of his proofs and evidence.
Keywords: khul; Judge Muhammad Khudhri Shnoyis; husband and wife; compensation